Dying of politeness - Davis, Geena (HarperOne, an imprint of HarperCollinsPublisher, 2022)
"From two-time Academy Award winner and screen icon Geena Davis, the surprising tale of her "journey to badassery"--from her epically polite childhood to roles that loaned her the strength to become a powerhouse in Hollywood."--